Efforts to Improve Teachers' Teaching Performance at SMAN 4 Medan - Darmilisani; Nuraini Kemalasari Istiqamah; Riska Fadhillah Hasibuan (International Forum of Researchers and Lecturers, 2024)
In achieving good education knowledge is strongly influenced by the performance of teachers in carrying out their duties so that teacher performance becomes an important demand to achieve the success of educators. The purpose of this study was to determine the efforts in improving the teaching performance of teachers at SMAN 4 Medan. This type of research is descriptive qualitative research with literature study research method. The results of this study explain that the factors that support the performance of teachers of SMAN 4 Medan such as, the effectiveness and efficiency of the performance of teachers of SMAN 4 Medan is less supportive of the learning system applied, Orientation and Responsibility of teachers of SMAN 4 Medan giving assignments/activities to their students is considered less on target, discipline in punctuality and work discipline, the initiative of teachers of SMAN 4 Medan in carrying out their duties is considered less good enough but teachers as much as possible carry out their goals as a teacher by always thinking positively and trying to attract students' interest in learning. Efforts to improve teacher performance can be done by coaching, supervising teacher work, providing motivation, and evaluating teacher performance.